2003
DOI: 10.1111/j.1525-1438.2003.13393.x
|View full text |Cite
|
Sign up to set email alerts
|

A real time optoelectronic device as an adjunct to the Pap smear for cervical screening: A multicenter evaluation

Abstract: We report on the results from a multicenter trial for a real time optoelectronic device as an adjunct to the Pap smear for cervical screening. TruScreen (Polartechnics Limited, Sydney, Australia) is an automated device which measures the response to optical and electrical stimulation of the cervix and returns a screening result in real time. Analysis was performed on a group of 651 subjects recruited at 10 centers. Cytology and histology analyses were performed by centralized laboratories, with the cytology cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 12 publications
3
25
0
5
Order By: Relevance
“…Moreover, subjectivity in the interpretation of Pap smear tests and need for consecutive doctor visits in case of abnormal results reveal an urgent need for additional, cost-effective methods for better results in the early diagnosis of cervical carcinoma. A multicenter trial by Singer et al that was performed in 671 patients in 10 centers showed sensitivities for histologically confirmed CIN 2/3 lesions by TruScreen™, Pap, and a combination of these two techniques as 70%, 69%, and 93%, respectively (11). In the same study, the sensitivities of the TruScreen™, Pap, and the combined test for CIN 1 positive (+) patients were 67%, 45%, and 87%, respectively.…”
Section: Roc Curvementioning
confidence: 48%
“…Moreover, subjectivity in the interpretation of Pap smear tests and need for consecutive doctor visits in case of abnormal results reveal an urgent need for additional, cost-effective methods for better results in the early diagnosis of cervical carcinoma. A multicenter trial by Singer et al that was performed in 671 patients in 10 centers showed sensitivities for histologically confirmed CIN 2/3 lesions by TruScreen™, Pap, and a combination of these two techniques as 70%, 69%, and 93%, respectively (11). In the same study, the sensitivities of the TruScreen™, Pap, and the combined test for CIN 1 positive (+) patients were 67%, 45%, and 87%, respectively.…”
Section: Roc Curvementioning
confidence: 48%
“…In multicenter studies, conducted in Australia and the UK, the sensitivity of the optoelectronic method for the detection of low−grade lesions within squamous epithelium was estimated at 67% (95% CI, 0.63-0.70), and for high−grade lesions at 70% (95% CI, 0.67-0.74) [15]. For comparison, the sensitivity of traditional cytodiagnostics was estimated at 45% (95% CI, 0.41-0.49) for LGSIL and 69% (95% CI, 0.65-0.72) for HGSIL.…”
Section: Discussionmentioning
confidence: 99%
“…The final element of the analysis is to compare the obtained model, characteristic for a given patient with a pattern. The pattern is a set of key parameters obtained from women of various origin, race, age, parity, etc [11]. Data gathered in the library are the collection of standard optoelectronics experience from studies in women with va− rious types of cervical pathology, particularly with CIN changes and cancers deriving from squamous epithelium and glandular epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Singer [3] используют Европейская федерация по КС и патологии шейки матки, Европейское общество гинекологической онкологии, Международная федерация по цервикальной патологии и КС, Российская ассоциация по генитальным инфекциям и неоплазии и др.…”
unclassified
“…Данная система отображения производит независимое от исследователя, количественное измерение и отображение эффектов ук-сусной кислоты. Это гарантирует значительное улучше-ние диагностики различия между цервикальной интра-эпителиальной неоплазией высокой степени и пораже-ний с низкой степенью злокачественности или в ее отсут-ствие, что было рассмотрено и изучено в работах ведущих специалистов данного направления [3,[18][19][20].…”
unclassified